Analisa Implementasi Technology Mobile Berbasis Bluetooth Android Untuk Smart Home - Taman Ginting; Didik Purwadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
Bluetooth Android has emerged as a viable choice of technology control for smart home for Light switch control uses an Android Smartphone communication media using Bluetooth. This system control can be used to support human needs in controlling its electronic equipment. This tool uses microcontroller technology, Android smartphones and Bluetooth. Bluetooth was initially developed as a cable replacement technology but properties such as low cost and high availability has led to the development of several control systems relying on Bluetooth signals. The characteristics of the Bluetooth device’s RSSI (Received Signal Strength Indication) value were analyzed in preliminary experiments. The best results of testing of algorithms to generate distance 1m greatest accuracy. From . Bluetooth and Smartphone can be seen that the maximum distance of Bluetooth can be connected without obstacles is 14 meters. The wall barrier has a thickness of 15 cm with a maximum distance of 10 meters. The data shows the level of barrier density affects the connection distance.From the results of the study note the effect on measurements include fingerprint grid size, algorithm and the amount of data from the location of the fingerprint data measurement area. From the results of the study with 10 m2 got 10.6 m results and 20 m2 with the results of 20.04 from the results of measurements and tests, it is known that the results of better light control in the range of 10 m2 or closer to the object / lamp.